PENGEMBANGAN MODUL EDUKASI KELUARGA ANAK JALANAN DI KAWASAN PASAR PUSAT PEKANBARU - Melly Surti Ningsih; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to develop an education module to families of street children and to test the validity of a education modules. The research method used is research and development with simplication of steps by Borg and Gall, namely: potential and problems, gathering information, product design, design validation, design revision, and product making. The instrument used was the assesment scale sheet, which was validated by 4 material experts, two guidance and counseling lecturers and two guidance and counseling teachers. The results showed that the education module to families of street children developed is a valid category to be used as educational materials to families of street children.Keywords: Research and development, Education module, Families of Street Children